2009
DOI: 10.1161/strokeaha.108.532853
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Structure and Function Is Correlated to Cognitive Performance and White Matter Hyperintensities in Older Hypertensive Patients With Subjective Memory Complaints

Abstract: Background and Purpose-Arterial stiffening and thickening and endothelial dysfunction may be associated with cognitive decline or white matter hyperintensities (WMH) independently of blood pressure level. We aimed to investigate, using an integrative approach, the relative contributions of structural and functional vascular factors to the degree of cognitive impairment (primary outcome) and the severity of WMH (secondary outcome) in elderly hypertensive patients with subjective memory complaints, a group prone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
173
3
30

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(212 citation statements)
references
References 49 publications
6
173
3
30
Order By: Relevance
“…Magnetic resonance imaging (MRI)-detected white matter hyperintensities (WMH) (Young et al 2008) are associated with vascular risk factors (Murray et al 2005) and with reduced cognitive ability and dementia in older adults (Leaper et al 2001;Firbank et al 2007). We previously found that WMH contribute 14% of the variance in cognitive ability at age 78, that WMH are linked to hypertension , and it is now widely accepted that WMH are an imaging biomarker of vascular disease (Kearney-Schwartz et al 2009, Raz et al 2007, Fischer et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI)-detected white matter hyperintensities (WMH) (Young et al 2008) are associated with vascular risk factors (Murray et al 2005) and with reduced cognitive ability and dementia in older adults (Leaper et al 2001;Firbank et al 2007). We previously found that WMH contribute 14% of the variance in cognitive ability at age 78, that WMH are linked to hypertension , and it is now widely accepted that WMH are an imaging biomarker of vascular disease (Kearney-Schwartz et al 2009, Raz et al 2007, Fischer et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…McNair questionnaire was also used in Wafta et al [32] and Kearney-Schwartz et al [33] studies, both of which addressed hypertensive older adults with MC investigating anti-hypertensive drug action on cognition. As a result, the studies showed that using drugs from the calcium channel blockers class was associated with better cognitive performance, regardless of blood pressure levels, usual cardiovascular risk factors and vessel structure, suggesting a protector effect from this pharmacological class.…”
Section: Discussionmentioning
confidence: 99%
“…High plasma von Willebrand factor levels were associated with the presence, and number of SBI, with periventricular but not deep WMHs, and with WMH burden. [77][78][79][80] Renin-angiotensin-aldosterone system…”
Section: Hemostatic Abnormalitiesmentioning
confidence: 99%